Transferrin Receptor‐Mediated Sequential Intercellular Nanoparticles Relay for Tumor Deep Penetration and Sonodynamic Therapy. Issue 6 (15th February 2019) - Zhang, Qiuhong; Wang, Ning; Ma, Ming; Luo, Yu; Chen, Hangrong
Abstract: Sonodynamic therapy overcomes the tissue penetration barrier of photo‐activated therapeutics, whereas the poor tumor penetration of sonosensitizers largely lowers therapeutic effectiveness. Here, a brand‐new strategy for achieving tumor deep penetration is developed by exploiting the cellular recycling transferrin (Tf). Specifically, a new type of nanosonosensitizer self‐assembled from Tf and organic sonosensitizer protoporphyrin IX is first designed, which exhibits expected biosafety, stability, and ultrasound‐activated cytotoxic reactive oxygen species (ROS) production capability ensuring in vivo administration. More importantly, the nanosonosensitizers inherit the unique transferrin receptor (TfR)‐mediated endocytosis and exocytosis behaviors of Tf, enabling specific binding to TfR‐overexpressed tumor cells and thereafter TfR‐mediated sequential intercellular delivery of nanosonosensitizers. Consequently, tumor deep delivery of sonosensitizers is achieved in TfR‐overexpressed HeLa tumors, which is considerably beneficial for desired tumor‐suppression effect with ROS‐mediated sonodynamic therapy protocol. Such a TfR‐mediated sequential intercellular relay strategy offers an innovative concept for the deep delivery of nanomedicines in tumors. Abstract : A transferrin receptor‐mediated sequential intercellular relay strategy is proposed to facilitate the deep penetration of nanoparticles in tumors. This strategy is demonstrated with a novel nanosonosensitizer facilely self‐assembled from transferrin and organic sonosensitizer protoporphyrin IX, which is proved to favor in vivo desired tumor‐suppression effect with a reactive oxygen species‐mediated sonodynamic therapy protocol.